Investigation into vibration propagation and attenuation characteristics of shield construction based on field measurement - Liang, Xu; Xu, Jian; Zhang, Yapeng; Zhou, Xuetao; Xie, Kuangqin; Yuan, Zonghao; Zhang, Min; Wu, Jian; Liu, Long (Frontiers in Earth Science, 2024)
Vibration caused by shield tunneling construction have adverse impacts on surrounding environment. To ascertain the influence of shield tunneling construction on ambient vibration, based on the shield tunnel project of Zhijiang Road in Hangzhou, the on-site vibration tests were carried out on the deep soil and surface during the excavation, and the vibration characteristics and vibration attenuation law during shield construction were investigated. The results show that the main frequency of vibration near the vibration source is wide, and the response components can be observed at 0–100 Hz. Under the filtering effect of the surface-covering soil layer, the high-frequency components of the vibration response are significantly attenuated, and the surface vibration is mainly distributed within 40 Hz. In the shield crossing, the deep measurement point is 5 dB higher than the vibration level of the same position on the surface. After the shield is pushed forward 20 m, the average attenuation of the surface vibration response is 10 dB, and the average attenuation of the deep vibration response is 12 dB.